Efficiency of Melamine Grafted Chitosan-based Magnetic Nanocomposite for Cationic Dye Adsorption: Kinetics, Isotherms, Thermodynamics - Hossein Dehghani; Sanaz Sajedi-Amin; Abdolhossein Naseri (Nanochemistry Research)
An adsorption activity of the functionalized magnetic nanoparticles with chitosan-melamine as a sorbent were studied for removal of dyes contaminants from aqueous solution. The morphology, structure, and size of the MA-CS@Fe3O4 nanocomposite have been investigated. The synthesized pH-sensitive adsorbent successfully adsorbs cationic dyes such as basic red and methyl blue. Adsorption experiments were carried out as batch studies at different contact time, pH, initial dye concentration, and adsorbent dosage. The dye adsorption equilibrium was rapid as it was achieved under 30 min of contact time with 5 mg adsorbent. The equilibrium data were analyzed by nonlinear Langmuir and Freundlich model for BR and MB adsorption. The best fitting results were achieved for Langmuir model and confirms that the adsorption of dyes are monolayer and the surface of MA-CS@Fe3O4 sorbent is homogeneous. The pseudo-second-order kinetics can describe the adsorption process for both MB and BR. Thermodynamic study showed that the adsorption was a spontaneous and endothermic process.